Penerapan Metode Design Thinking pada Perancangan Ulang UI/UX Website Leaps Kalbis Institute - Jonatan Glensius; Mira Ziveria (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2026)
In utilizing technology and the internet, learning and teaching activities at the Kalbis Institute create an information system in the form of a website. The website is named LEAPS which functions as an information service for all students and teachers at the Kalbis Institute. In this study, researchers will discuss the problems that are faced by Kalbis Institute students when they are using LEAPS. This study aims to help solve problems with interface design solutions. The researcher used the design thinking method as a research method, the Google form as a tool for finding questionnaire data, the Slovin formula as a determinant of the sample space, and a user experience questionnaire as a testing tool. In the prototype designs that have been tested by researchers, researchers get excellent results on the attractiveness scale, the clarity scale gets the excellent predicate, the efficiency scale gets the excellent predicate, the accuracy scale gets the good predicate, the stimulation scale gets the good predicate, and the novelty scale gets the excellent predicate. From these results, it is necessary to increase the accuracy and stimulation scale in order to get an excellent predicate.